2017
DOI: 10.1371/journal.pone.0178701
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and drought characteristics in the loess hilly-gully region of China from 1957 to 2014

Abstract: The loess hilly-gully region is a focus region of the “Grain for Green” program in China. Drought is the main problem in the study region. Precipitation and temperature are two indicators that directly characterize climatic drought. A thorough analysis of the precipitation, temperature and drought characteristics of the loess hilly-gully region can clarify the current water and heat conditions in the region to improve regional water resource management and provide a reliable reference for effectively improving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Among these methods, the Mann-Kendall trend test is the most popular method and is employed in many regions across the world. Zhao and Li [22] thoroughly analyzed climate change trends and characteristics between 1957 and 2015 at 11 synoptic stations along the loess hilly-gully region by using a combination of wavelet analysis, Spearman's rho test, linear trend estimation, the Mann-Kendall test, trend-free pre-whitening, and the abrupt change test. Adarsh and Janga Reddy [23] analyzed annual rainfall data in four subdivisions of southern India using the nonparametric Mann-Kendall test, linear regression, andŞen's slope estimator methods.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, the Mann-Kendall trend test is the most popular method and is employed in many regions across the world. Zhao and Li [22] thoroughly analyzed climate change trends and characteristics between 1957 and 2015 at 11 synoptic stations along the loess hilly-gully region by using a combination of wavelet analysis, Spearman's rho test, linear trend estimation, the Mann-Kendall test, trend-free pre-whitening, and the abrupt change test. Adarsh and Janga Reddy [23] analyzed annual rainfall data in four subdivisions of southern India using the nonparametric Mann-Kendall test, linear regression, andŞen's slope estimator methods.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research results suggested that the low efficiency in dominant ecological functions at existing plantations could the effects of the increasing type and frequency of human activities that alter the climate, topography, and soil environment, forest ecosystems have been changing slowly and continuously [16,17]. For example, global warming has increased in severity, which caused soil and water losses, soil water imbalances, and changes to the physical and chemical properties of the soil environment, as a result, vegetation does not grow normally and dominant ecological functions are not fully carried out in the natural environment [18][19][20]. The internal factor is mainly an unreasonable forest structure that leads to low-efficiency ecological functions [21] because the structure determines the function.…”
Section: Introductionmentioning
confidence: 99%